s27nvil
contestada

x + 4 + 2x + 5
10x – 3x + 7
5x + 6y + 2xy + 4x – 2y
7t + 2r – 3t + r
14 + 11p – 12
8q – 3t + 4q + 9
may u please simplify these

Respuesta :

Step-by-step explanation:

a)x + 4 + 2x +5

= x + 2x + 4 + 5

= 3x + 9

b)10x - 3x + 7

=7x + 7

c)5x + 6y + 2xy + 4x - 2y

=5x + 4x + 6y - 2y + 2xy

=9x + 4y + 2xy

c)7t + 2r - 3t + r

=7t - 3t + 2r + r

=4t + 3r

d)14 + 11p - 12

=14 - 12 + 11p

=2 + 11p

e)8q - 3t + 4q + 9

=8q + 4q + 3t + 9

=12q + 3t + 9

1: 3x + 9
2: 7x + 7
3: 2xy + 9x + 4y
4: 4t + 3r
5: 11p + 2
6: 12q - 3t +9
ACCESS MORE